Enhancing visuospatial learning: The benefit of retrieval practice. - KANG, SVAN H. K. (Memory & Cognition, 2010)
Studies examining the beneficial effect of testing on memory have relied almost exclusively on verbal materials. Whether testing can improve the learning of novel, abstract visuospatial information was investigated, using Chinese characters as study stimuli. Subjects with no prior Chinese language experience studied English words paired with their Chinese equivalents. Subsequently, they either restudied the pairs twice or attempted to retrieve covertly the Chinese characters twice (with feedback provided afterward). The durations of the study and the retrieval/feedback trials were equated. On a final test given after 10 min (Experiment 1) or 24 h (Experiment 2), the subjects who had practiced retrieval were more accurate at writing/drawing the Chinese characters than were those who had studied repeatedly. The same result was replicated when learning condition was manipulated within subjects (Experiment 3). In predictions of future performance made after training, however, the subjects seemed unaware that retrieval practice was more effective than repeated studying. Testing enhances visuospatial learning, with potential implications for learning a foreign language that uses a writing script different from one's language: Repeated retrieval from memory trumps repeated studying.